(γ-Methoxy propyl amine)2PbBr4: a novel two-dimensional halide hybrid perovskite with efficient bluish white-light emission. Issue 8 (5th March 2021) - Li, Yezhan; Ji, Chengmin; Li, Lina; Wang, Sasa; Han, Shiguo; Peng, Yu; Zhang, Shuhua; Luo, Junhua
Abstract : A 2D hybrid perovskite based on alkoxyamine cations shows bright bluish white-light emission with a high PLQE of 6.85%. Abstract : White-light emission in lead halide hybrid perovskites has attracted increasing attention due to their significant applications in the field of light-emitting devices. Despite tremendous efforts, two-dimensional (2D) white-light emissive perovskites with high photoluminescence quantum efficiency (PLQE) remain scarce. In this work, by using alkoxyamine organic cations as a template, we successfully synthesized a new 2D layered hybrid perovskite, (γ-methoxy propyl amine)2 PbBr4 (γ-MPAPB ), which exhibits bright bluish white-light emission with an excellent color rendering index (CRI) of 85 and a high PLQE of 6.85%. Photoluminescence measurements show a correlation between self-trapped excitons and white-light emission. To the best of our knowledge, this is the first demonstration of a 2D hybrid perovskite with efficient white-light emission based on alkoxyamine cations. This work emphasizes the strategy of introducing alkoxyamine cations into 2D layered hybrid perovskites to design efficient white-light emissive perovskite semiconductors.